Innovation Priorities for Power Engineering: A Case of Sectoral Foresight - Alexey Dub; Sergey Shashnov (Foresight and STI Governance, 2007)
The article reviews the results of Foresight project on the definition of innovation priorities for power engineering. Their support will facilitate the introduction of high-tech and resource-saving technologies, and production of new competitive products and the development of export-oriented industries.